Cyril Hovorun. Scaffolds of the Church: Towards Poststructural Ecclesiology. - Oleksandr Geychenko (Богословські роздуми: Східноєвропейський журнал богословʼя)
Book reviwe: Scaffolds of the Church: Towards Poststructural Ecclesiology. By Cyril Hovorun. Eugene, OR: Cascade Books, 2017. xii, 262 pp.; ISBN 9781498284202 (pbk.); 26.00 GBP